2014
DOI: 10.18632/oncotarget.2576
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological induction of cell surface GRP78 contributes to apoptosis in triple negative breast cancer cells

Abstract: Breast cancer tumor with triple-negative receptors (estrogen, progesterone and Her 2, receptors) is the most aggressive and deadly subtype, with high rates of disease recurrence and poor survival.Here, we show that induction in cell surface GRP78 by doxorubicin and tunicamycin was associated with CHOP/GADD153 upregulation and increase in apoptosis in triple negative breast cancer tumor cells.GRP78 is a major regulator of the stress induced unfolded protein response pathway and CHOP/GADD153 is a pro-apoptotic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 60 publications
(57 reference statements)
3
26
1
3
Order By: Relevance
“…These results coincide with previous reports in which we demonstrated that hypoxia induced a significant increase in cell surface GRP78 on endothelial cells, cardiomyocytes and neurons [10,12,13]. The re-localization and overexpression of GRP78 in the cell surface of tumor cells was also reported to be induced by ER stress produced by microenvironmental factors and chemotherapy drugs [32,33]. Moreover, STZ is known to elicit an immune and inflammatory reaction that can probably induce cell surface GRP78 expression in this model of diabetes type 1 [22].…”
Section: Adopep Peptide Inhibited Apoptosis In Ins1e Cells Exposed Tosupporting
confidence: 92%
See 1 more Smart Citation
“…These results coincide with previous reports in which we demonstrated that hypoxia induced a significant increase in cell surface GRP78 on endothelial cells, cardiomyocytes and neurons [10,12,13]. The re-localization and overexpression of GRP78 in the cell surface of tumor cells was also reported to be induced by ER stress produced by microenvironmental factors and chemotherapy drugs [32,33]. Moreover, STZ is known to elicit an immune and inflammatory reaction that can probably induce cell surface GRP78 expression in this model of diabetes type 1 [22].…”
Section: Adopep Peptide Inhibited Apoptosis In Ins1e Cells Exposed Tosupporting
confidence: 92%
“…Earlier studies demonstrated the correlation of cell surface GRP78 over expression and apoptosis in normal and cancer cells [10,[12][13][14]33]. The addition of ADoPep peptide to Ins1E cultures inhibited significantly the percent of STZ treated cells undergoing apoptosis.…”
Section: Adopep Peptide Inhibited Apoptosis In Ins1e Cells Exposed Tomentioning
confidence: 94%
“…Based on those and previous findings in our laboratory [26,27], we hypothesized that chemotherapy may induce ER stress not only in the tumor tissue, but also in immune cells, which affect the response to the treatment. Therefore, in this study, we focused on the ER stress response in leucocyte subpopulations exposed to neoadjuvant breast cancer treatment.…”
Section: Introductionmentioning
confidence: 74%
“…Estudios utilizando líneas celulares de cáncer de colon muestran que las líneas celulares HCT116 y HM7 alcanzan hasta un 85% de frecuencia de células que relocalizan GRP78 en la membrana plasmática (Hardy et al, 2012). Por otro lado, diversos estudios han demostrado que los niveles de GRP78 en la superficie celular varían dependiendo de la línea celular, por ejemplo, la línea celular MDAMB468 de cáncer de mama tiene niveles mayores de GRP78 de superficie en comparación a la línea BT474 (Raiter et al, 2014).…”
Section: Grp78 Isotipounclassified
“…El análisis de citometría de flujo muestra que las células de LLA provenientes de médula ósea muestran una frecuencia media mayor de células que relocalizan GRP78 que su contraparte de sangre periférica e individuo sano, muy similar a la tendencia observada en las líneas celulares de LLA evaluadas. Las razones por las que hay una mayor frecuencia de células GRP78+ en individuos pediátricos en comparación a las líneas celulares de LLA no han sido establecidas, sin embargo, se ha demostrado que en otros modelos de cáncer, como el de mama, moléculas como la Doxorubicina o Taxotere inducen la sobreexpresión y relocalización de GRP78 hacia la membrana plasmática, incrementándose la frecuencia de células GRP78+ hasta un 50±7.7% en comparación a la frecuencia original (7%) (Raiter et al, 2014). El microambiente tumoral caracterizado por hipoxia, privación de glucosa o una alteración en la homeostasis del Ca 2+ podrían contribuir en la aparición de células leucémicas que relocalizan GRP78 en la LLA, principalmente en médula ósea.…”
Section: Grp78 Isotipounclassified